Evaluation of Anti-Helicobacter pylori Activity of Methanol Extracts of Some Species of Stachys and Melia - M Khanavi; M Safavi; F Siavoshi; A Fallah Tafti; M Hajimahmoodi; A Hadjiakhoondi; Sh Rezazadeh; A Foroumadi (Institue of Medicinal Plants, ACECR, 2008)
Background: The gram-negative bacterium Helicobacter pylori (H. pylori), identified in 1982, is now recognized as the primary etiological factor associated with the development of gastritis and peptic ulcer disease. The growing problem of antibiotic resistance by the organism demands the search for novel compounds from plant based sources. Objective: The present study is aimed at evaluating the anti-Helicobacter pylori activity of 10 Iranian plant extracts on clinical isolates of H. pylori. Methods: Gastric biopsy samples were obtained from patients presenting with gastroduodenal complications. H. pylori was isolated from the specimens following standard microbiology procedures. The disk diffusion method was used to determine the susceptibility of 12 isolates to methanol plant extracts (Fruit and leaves of Melia azedarach, Melia indica and aerial parts of Stachys setifera, Stachys turcomanica, Stachys trinervis, Stachys subaphylla, Stachys byzanthina, Stachys persica, Stachys inflata, Stachys laxa). Results: The plants tested at 8 mg/disc concentration demonstrated anti-Helicobacter pylori activity with zone diameters of inhibition ranging from 12-38 mm. Of these, Stachys setifera (aerial parts), Melia indica (Fruit) and Melia azedarach (leaves) showed the most potent anti -H. pylori activity on the isolates. Conclusion: Due to the rise in antibiotic resistance, new sources of anti-H. pylori drugs are needed. The use of medicinal plants may have potential benefit in eradicating such problems. According to the results of this study, further studies will be necessary to investigate the effects of other plants of Iran against H. pylori infection.